2017
DOI: 10.1159/000484691
|View full text |Cite
|
Sign up to set email alerts
|

CRF35-AD as the Main Circulating Genotype of Human Immunodeficiency Virus Type 1 Infection in Iran: A Phylogenetic and Demographic-Based Study

Abstract: Finding the predominant circulating subtype of human immunodeficiency virus type 1 (HIV-1) and surveying co-infection with other infectious viruses are crucial to making preventive decisions. To this end, 50 Iranian HIV-positive patients made up of 37 men and 13 women were selected. Most of the HIV-positive patients (70%) were intravenous drug users (IDUs), and 48 and 32% of patients were co-infected with HCV and HBV, respectively. The rate of simultaneous infection with HIV, HCV, and HBV was found to be 6%. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
(18 reference statements)
0
2
1
Order By: Relevance
“…They suggested African origins, Uganda and Kenya, for the HIV circulating in this large region. However, the phylogenetic relationship findings in the present study showed radical changes to the CRF35-AD, which is the predominant subtypes in other parts of Iran (22).…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…They suggested African origins, Uganda and Kenya, for the HIV circulating in this large region. However, the phylogenetic relationship findings in the present study showed radical changes to the CRF35-AD, which is the predominant subtypes in other parts of Iran (22).…”
Section: Discussioncontrasting
confidence: 73%
“…The reference sequences were ob-tained from the Gene bank (www.ncbi.nlm.nih.gov) and HIV database (www.hiv.lanl.gov). The phylogenetic tree was constructed by MEGA software (version X) with the maximum-likelihood method and GTR substitution model with 1000 bootstrap values (Figure 1) (GeneBank accession: MK968931-41) (22). The data were analyzed using SPSS software (version 13.0; SPSS Inc, Chicago).…”
Section: Human Immunodeficiency Virus Rna Assaysmentioning
confidence: 99%
“…Despite the joint transmission routes between HIV-1 and HTLV-1, they lead to remarkable different diseases. The infection by HIV-1 results in the acquired immunodeficiency syndrome (AIDS) associated with CD 4 þ T cell depletion which results in many mortal diseases [7,8]. HTLV-1 causes two main diseases including Adult T-cell leukaemia/lymphoma (ATLL) and HTLV-1 Associated Myelopathy/Tropical Spastic Paraparesis (HAM/TSP) and also some other disorders [9,10,11].…”
Section: Introductionmentioning
confidence: 99%